ANALISIS KESALAHAN PENGGUNAAN EJAAN PADA TEKS BERITA SISWA KELAS VIII-A SMP NEGERI 2 TELUK DALAM - Yulianis Riwati Duha (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The problem with this research is that errors in using capital letters and the use of punctuation marks, commas and brackets in writing news texts are still relatively low. The aims of this research are. This type of research is a qualitative approach with descriptive methods. The subjects in the research were 20 students in class VIII-A of SMP Negeri 2 Telukdalam. The result of the research showed that there were 16 capital letters and 21 in the punctuation marks news texts as evidenced by photos of students assignments. Suggestion put forward in this research 1) Indonesian language teachers should provide students with a thorough understanding of how to use spelling in the news according to correct spelling rules. 2) for students, they are required to pay attention to writing good and correct news texts according to spelling standards so as not to hinder the reader’s understanding of the news written 3) for researchers, this research is anticipated to teach Indonesian language and literature teachers in the future important lessons about how to recognize students’ learning deficiencies better and how to use correct spelling.